VD_FINDINFO Décision / 2014 / 286 vom 7. Februar 2014 - VD Tribunal cantonal (2014)
INJURE, DIFFAMATION, CLASSEMENT DE LA PROCÉDURE, RACISME, ASSISTANCE JUDICIAIRE | 173 ch. 1 CP, 177 CP, 261bis CP, 319 CPP (CH), 393 al. 2 let. a CPP (CH), 429 al. 1 let. a CPP (CH)